Sexual Deviation Factors in HIV Men Who Have Sex With Men (MSM) - Rusdianingseh Rusdianingseh; Bisma Aditiya Putra; Raden Khairiyatul Afiyah; Siti Maimunah; Nety Mawarda Hatmanti; Muhamad Khafid (Jurnal Keperawatan Respati Yogyakarta, 2023)
This behavior is deviant sexual behavior because it appears based on deviant sexual orientation, causing a person's tendency to direct his feelings of attraction, emotional and sexual, to men. The problem of homosexual deviant sexual behavior has no end to be discussed. This problem is a sensitive issue involving social, cultural, moral, and ethical aspects of society and rules in religion. However, it can still be found in MSM groups who are HIV positive and who are still actively carrying out risky activities whose impact will expand and increase the prevalence of HIV cases, especially in the MSM group. This study contributes to analyzing the factors of sexual deviation in the HIV MSM group. The study used descriptive research. The population in this study was 56 groups of sex men with HIV men who were still actively engaging in sexual activities. Sampling using the technique Non-Probability Sampling with total type sampling is 56 respondents. The research instrument used a questionnaire. Data were analyzed by calculating the highest number of frequencies on the questionnaire (Frequency Distribution). The results show that of the five factors underlying the HIV MSM group who are still carrying out risk activities were categorized as having sufficient knowledge (62.5%), having an addiction (60.7%), economic factors (60.7%), having enough influence from peers (58.9%), influenced by authoritarian and permissive parenting styles (32.1%) and spiritual factors (48.2%. Sufficient knowledge factors are the most influential factors in sexual deviations that occur primarily in the HIV MSM group who are respondents, so it is expected to be able to focus more on prevention programs on the factors affecting the group. It is recommended to create a new program to reduce the impact of sexually deviant behavior on HIV MSM groups. Such as making an effective activity program (which can generate money) as a filler in spare time and a substitute for these sexual deviation activities. Psychological and spiritual approach program (Spiritual and Mental Health Awareness) where this program aims to improve spiritual (closeness to God) and also psychological so as not to have risky tendencies